Measuring economic insecurity - Walter Bossert; Conchita D'Ambrosio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
We provide an axiomatic treatment of the measurement of economic insecurity, assuming that individual insecurity depends on the current wealth level and its variations experienced in the past. The first component plays the role of a buffer stock to rely on in case of an adverse future event. The second component determines the confidence an individual has on his ability to overcome a loss in the future. Experiences in the recent past are given higher weight than experiences that occurred in the more distant past. Two classes of measures are characterized with sets of plausible and intuitive axioms.
Keywords: D63; 330; insecurity; wealth streams; economic index numbers